Economic analysis of oil and gas engineering operations - Abdel-Aal, Hussein K. (Boca Raton, FL : CRC Press, 2021)
"This book focuses on economic treatment of petroleum engineering operations and serves as a helpful resource for making practical and profitable decisions in oil and gas field development. This work will be of value to practicing engineers and industry professionals, managers, and executives working in the petroleum industry who have the responsibility of planning and decision making, as well as advanced students in petroleum and chemical engineering studying engineering economics, petroleum economics and policy, project evaluation and plant design"--
OCLC-licensed vendor bibliographic record.
Keywords: Petroleum industry and trade; Oil fields -- Economic aspects; Gas fields -- Economic aspects; TECHNOLOGY / Petroleum; TECHNOLOGY / Engineering / Chemical & Biochemical